(Pada PT.Gunung Agung Cabang mall Citra Land, Simpang Lima Semarang) - Silalahi, Frisca Aulia; Magnadi, Rizal Hari (Faculty of Economics and Business Diponegoro University, 2016)
This Study aims to examine the effect of trust, commitment, satisfaction, loyalty, reliability salesperson to the quality of relationships at PT Gunung Agung Branch of Citra Land mall, Simpang Lima, Semarang. This study uses a trust, commitment, satisfaction, loyalty, reliability salespeople as independent variables and quality of relationships as the dependent variable. This study uses qualitative data analysis with data collection methods using interviews and quantitative is questionnaires. The study involved five employees who are close to the supplier as respondent questionnaires and interviews and some suppliers in an interview. Based on the results of qualitative research, the reliability of salespeople do not affect the quality of relationships GUNUNG AGUNG PT Citra Land Branch mall, Simpang Lima, Semarang